A novel volcanic gas observation technology to improve eruption prediction models.
Current volcano monitoring techniques essentially revolve around geophysical observations. Building upon the consensus that volcanic gases are another determining factor in volcanic eruptions-one that cannot be ignored-the BRIDGE project has set out to develop gas monitoring technologies whose combination with geophysics should help improve predictions.